Use of Soil Remineralizer to Replace Conventional Fertilizers: Effects on Soil Fertility, Enzymatic Parameters, and Soybean and Sorghum Productivity - Letícia Nayara Fuzaro Rodrigues; Wander Luis Barbosa Borges; Viviane Cristina Modesto; Naiane Antunes Alves Ribeiro; Nelson Câmara de Souza; Vitória Almeida Moreira Girardi; Aline Marchetti Silva Matos; Bárbara Pereira Christofaro Silva; Fernando Shintate Galindo; Marcelo Andreotti (Agriculture)
The reliance on soil acidity correctives and mineral fertilizers poses a threat to food production due to the finite nature of these resources and their susceptibility to price volatility from importation. Soil remineralizers have emerged as a sustainable alternative. This study assessed silicate agrominerals as soil remineralizers to replace limestone, gypsum, and conventional fertilizers in a no-tillage system. Conducted in a tropical climate on sandy/medium-textured Ultisol, twelve treatments (combinations of liming, gypsum, mineral fertilization, and remineralizer) were tested for their effects on soybean and sorghum agronomic traits. Applying a remineralizer at 2500 kg ha−1 enhanced soybean productivity by 15% and sorghum by 35% in succession, along with increases in P, S, Ca, Mg, sum of bases (SB), cation exchange capacity (CEC), base saturation (V%) in the 0–0.20 m layer and organic matter in the 0–0.40 m layer, benefiting soil microbiological parameters, with the treatment combining all four products improving soil fertility; however, for better crop productivity, split applications appear to be an alternative to avoid nutrient imbalance. Due to the finer particle size of the remineralizer, which allows faster nutrient release, further research is recommended to investigate the long-term impacts on soil microbiota dynamics, optimal doses and combinations, and economic viability across various soil types and climates.